Measurement of the CKM angle γ in B± → DK[ast](892)± decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
Measurements of CP observables and the CKM angle γ are performed in B± → DK∗(892)± decays, where D represents a superposition of D0 and D0 states, using the LHCb dataset collected during Run 1 (2011–2012) and Run 2 (2015–2018). A study of this channel is presented with the D meson reconstructed in two-body final states K±π∓, K+K− and π+π−; four-body final states K±π∓π±π∓ and π+π−π+π−; and three-body final states K0 Sπ+π− and K0 SK+K−. This analysis includes the first observation of the suppressed B± → [π±K∓]DK∗± and B± → [π±K∓π±π∓]DK∗± decays. The combined result gives γ = (63 ± 13)◦.